Development of a Health Impact Assessment Implementation Model: Enhancing Intersectoral Approaches in Tackling Health Inequalities- A Mixed Methods Study Protocol [version 3; peer review: 2 approved, 1 approved with reservations] - Paul Kavanagh; Tara Kenny; Monica O'Mullane; Katherine Smith; Kirsty Nash; Sheena M. McHugh; Uduak Archibong (HRB Open Research)
Public health research presents compelling evidence that health is socially determined. To address structural inequalities and inequities in health, public policies require intersectoral development and implementation. Health Impact Assessment (HIA) is an established approach for analysing potentially detrimental health impacts of policies, programmes, and projects, as well as potentially positive impacts and opportunities. National public health policy, Healthy Ireland (2013–2025), endorses an intersectoral whole-of-system approach to ensure that health is a central part of all relevant policy areas. HIA is endorsed in this policy as one way to drive this agenda. Synergising with this policy commitment for HIA, the all-island Institute of Public Health Ireland produced revised HIA guidance in 2021. Two HIAs will be carried out as part of this project, including one at a local policy level, addressing the Cork City Development Plan (2022–2028), and the second HIA at a national policy level, addressing the Irish Government’s Climate Action Plan (2024). The updated HIA guidance will be used in the conduct of these HIAs. This research project involves a co-creation of a Health Impact Assessment Implementation Model by employing an action research approach with implementation science frameworks to the conduct of the two HIAs. Therefore, the process of doing the HIAs will form the basis for the research study. In order to enhance meaningful community involvement in HIA in Ireland, the project will co-create a Community Engagement Toolkit for HIA. This Model will strengthen researcher, policy actor, practitioner, community, and voluntary sector capacity to collaboratively develop and implement intersectoral and equitable policy responses to major population health issues.